Evaluating the impact of artificial intelligence applications on accelerating the project life cycle and increasing its flexibility: A comparative study of agile and traditional management methodologies - Mohammed, Anwar Mohammed Gismallah (Journal of Economic, Administrative and Legal Sciences, 2025)
The research aimed to identify the impact of using artificial intelligence applications on accelerating the project life cycle and project flexibility (traditional and agile management). The research problem stems from the significant development witnessed by the Kingdom of Saudi Arabia in the use of artificial intelligence in project management, which raises questions about its impact on accelerating the project life cycle and increasing its flexibility. The main challenge lies in exceeding the specified time frame for project implementation, which necessitates the use of modern technologies and effective management practices. The theoretical importance of the research lies in the extent to which it contributes to expanding the theoretical understanding of artificial intelligence techniques in the project life cycle by comparing agile and traditional management, which fills the current research gap and provides accurate analytical data. The practical importance is that the research provides practical strategies and recommendations for project management in Saudi Arabia using artificial intelligence, which enhances flexibility and adaptation to rapid changes. The study population consists of all project workers in the Kingdom of Saudi Arabia. The study sample included (91) male and female workers from the research population. The study relied on the descriptive design as a study approach and used the questionnaire as a study tool. The study concluded that there was a statistically significant effect of using artificial intelligence applications on project flexibility and accelerating the project life cycle. The study recommended educating employees about the benefits of artificial intelligence and explaining how artificial intelligence contributes to improving project efficiency, increasing productivity, reducing risks, and improving work quality.
Keywords: Artificial intelligence applications; Project life cycle; Project flexibility; Agile and traditional management